Kelemahan Perlindungan Hukum terhadap Perempuan Dari Kekerasan Seksual di Ruang Publik - Wahyu Krisnanto; Martika Dini Syaputri (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Indonesia is one of the countries that has ratified the Declaration on the Convention on the Elimination of all Forms of Discrimination Against Women (CEDAW) and follow up with the issuance of various laws and implementing regulations. Even though Indonesia has ratified the Convention on the Elimination of all Forms of Discrimination Against Women and has published various legal instruments for the protection of women, referring to the results of the 2018 National Commission on Violence Against Women there were 348,446 cases of Violence Against Women, of which 3,528 cases occurred in the public sphere and 2,670 cases of violence in the form of sexual violence. Based on these problems, a study was conducted to find out how people's perceptions of women's body autonomy and other forms of sexual violence in public spaces were experienced by women. Theoretical understanding is expected to be used as a basis for legal reform to be more effective in protecting women from sexual violence in the public sphere. This research is legal research with a social science approach. With empirical research, the method used is a qualitative research method by conducting structured interviews with women and in-depth interviews with police officers. The analysis technique that will be used is descriptive qualitative. From the results of the study obtained data, that sexual violence is caused by the unequal power relations between men and women resulting in the view of women as other people. Women do not have autonomy over their bodies. The female body is only used as an object of sexual attraction for men. The dominance of masculinity does not only manifest in the form of violence, but also the norms and rules of law. Legal norms and rules are more nuanced masculine that is not sensitive to the existence of women. There is a need for existing legal reforms to show the real form of gender equality.